Kinematic analysis and development of cable-driven rehabilitation robot for cerebral palsy patients. (27th February 2023) - Aria, H Partovi; Ahrabi, M; Allahverdi, F; Korayem, M Habibnejad
This study aimed to analyze the kinematic development of a rehabilitation cable robot for patients with cerebral palsy problems. For this purpose, the walking pattern of a healthy person was analyzed in the robot by extracting his kinematic model. Therefore, a seven-link model was considered, and changes in the mass center of the links and then movements during the gait cycle were obtained with the angles related to joint changes. Next, the person's integration with the rehabilitation cable robot was investigated with the resolution of the direct kinematic problem. In addition, the change-related outputs of the cables were obtained by the person's movement and the attached belt. The robot was further proposed because the specific change diagram of the cables facilitates understanding how much motor torque is needed to change the length of the cable. It is noteworthy that the static person balance is provided in the existing rehabilitation robots. However, in this structure, the balance is done by the six degrees of freedom robot so that the robot can return the person to the original path when he loses his balance. Cable systems for the lower limbs (thighs and shanks) are also simulated to rehabilitate the patient. The obtained results from the simulation and the obtained output from kinematic equations for lower limb movements were also compared, and the highest deference was 2.2, 1.8, 1.8, and 1.5% for shank-back, shank-front, thigh-back, and thigh-front of the leg in the corresponding points in the outputs of both software, respectively.